SHARIA EMPLOYEE COOPERATIVE SERVICE SYSTEM PT. PUPUK ISKANDAR MUDA - Hayati, Nurul; Izza, Nurul; Rahmadani, Zuhra; Fajiral, Raihan; Sinta, Irada (RADJA PUBLIKA, 2023)
This study aims to formulate the problem